2008
DOI: 10.1080/15374410802359858
|View full text |Cite
|
Sign up to set email alerts
|

The Family Check-Up in Early Childhood: A Case Study of Intervention Process and Change

Abstract: This article describes a case study in the use of the Family Check-Up (FCU), a family-based and ecological preventive intervention for children at risk for problem behavior. The FCU is an assessment-driven intervention that utilizes a health maintenance model; emphasizes motivation for change; and offers an adaptive, tailored approach to intervention. This case study follows one Caucasian family through their initial assessment and subsequent treatment for their toddler daughter's conduct problems over a 2-yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3
2

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 24 publications
1
27
0
1
Order By: Relevance
“…Shaw et al (2006) detailed the first in a series of notable studies of the FCU program in early childhood. These studies demonstrated the positive longitudinal effects of the program on very young children who were identified as at-risk for early conduct problems Dishion et al, 2008;Gill, Hyde, Shaw, Dishion, & Wilson, 2008;Lunkenheimer et al, 2008;Moilanen, Shaw, Dishion, Gardner, & Wilson, 2010;. Those children of low-income families, who were randomly assigned to the FCU condition, demonstrated improvements in school readiness (inhibitory control and language development) through the effects of the FCU on parents' provision of increased positive behavioral support.…”
Section: Ecofitmentioning
confidence: 95%
“…Shaw et al (2006) detailed the first in a series of notable studies of the FCU program in early childhood. These studies demonstrated the positive longitudinal effects of the program on very young children who were identified as at-risk for early conduct problems Dishion et al, 2008;Gill, Hyde, Shaw, Dishion, & Wilson, 2008;Lunkenheimer et al, 2008;Moilanen, Shaw, Dishion, Gardner, & Wilson, 2010;. Those children of low-income families, who were randomly assigned to the FCU condition, demonstrated improvements in school readiness (inhibitory control and language development) through the effects of the FCU on parents' provision of increased positive behavioral support.…”
Section: Ecofitmentioning
confidence: 95%
“…The parent was also offered follow-up sessions that focused on parenting practices, other family management concerns (e.g., co-parenting), and contextual issues (e.g., day care, partner relationship, housing). The MI approach is especially prominent in the initial interview and feedback sessions and pervades later sessions as needed, depending on parent motivation and engagement (Gill et al, 2008). …”
Section: Methodsmentioning
confidence: 99%
“…The meeting would provide feedback on the child's behavior (e.g., your child is in the 99 th percentile for their age in disruptive behaviors) gathered by teacher ratings on the standardized measure (i.e., the CBCL/TRF). This meeting would also include motivational strategies to encourage parents to engage with community supports or to consider approaches to change child behavior (for a case study example of feedback see Gill et al, 2008). Children whose parents that would not receive feedback would be monitored meaning that their teachers would continue to fill out questionnaires on the child's behavior at each assessment point.…”
Section: Head Start Smartmentioning
confidence: 99%